Opting out of court? Reputation and informal norms in private equity - Kobi Kastiel; Yaron Nili (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
Private equity, an industry characterized by high-stake investments and complex contractual arrangements, operates almost entirely outside of courts. Despite the substantial financial stakes involved - billions of dollars locked in for years - and the potential for fiduciary conflicts, litigation between limited partners (LPs) and general partners (GPs) who manage the investment is exceptionally rare. In stark contrast to public markets, where shareholder litigation plays a prominent role in deterring misconduct and shaping corporate norms, the private equity world is largely defined by its absence. The puzzle, then, is this: In an industry where fiduciary breaches or misaligned incentives are not uncommon, why do LPs almost never turn to courts to enforce their rights? Drawing on proprietary documents, public records, and qualitative interviews with market players, this article provides the first account of the rarity of litigation in private equity and the ecosystem of extralegal relations and informal norms that serve as a partial substitute for formal legal channels. This article makes three contributions to the literature on private equity. First, using hand-collected data, the article provides an empirical account of the non-litigious private equity landscape and its underlying causes. It also highlights how opting out of court is a result of reputational concerns, contractual barriers, and institutional disincentives. Second, the article investigates how private equity resolves disputes and enforces norms without recourse to courts. Based on a unique set of interviews with LPs, GPs, and legal advisors, this article sheds light on the alternative mechanisms that dominate the private equity landscape. Third, the article explores the implications of this non-litigious environment for investor protection, market efficiency, and regulatory oversight, questioning whether reliance on reputation and extralegal mechanisms is sustainable in the face of growing industry complexity.
Keywords: 330; Private Equity; Reputation; Soziale Norm; Gerichtsbarkeit; Konfliktregelung; Rechtsdurchsetzung; USA